Students’ Perception on Grammo as an Alternative Teaching Media in Grammar Mastery - Lidiyatul Izzah; Muhamad Sofian Hadi; Vira Luthfia Pratiwi (Universitas Teknokrat Indonesia, 2021)
AbstractConsidering some of the problems faced by secondary school students, especially senior high school students, who still find it difficult to remember grammar material and the lack of innovation in teaching media in the classroom, as well as the teacher's lack of attention to students, researchers are trying to find a way out of this problem by using Grammo. The aim of this study was to determine the students’ perception on Grammo as an alternative teaching media in grammar mastery to XII grade at SMK Kesehatan Letris Indonesia 2, Pamulang, Tangerang Selatan, Banten and MA Daarus Saadah, Cipondoh, Kota Tangerang, Banten. A survey with a descriptive quantitative approach was the research method used. The data collection technique used questionnaire in the form of a Likert Scale. The participants of this research analysis was class XII who were randomly selected as many as 100 students. The data analysis technique uses hypothesis testing based on validity and reability tests. Based on the results of the data processing where the probability value (p) is 0,05, it can be concluded that Grammo can be used as an alternative media in grammar mastery. Based on these results, it is hoped that Grammo can be used and make the classroom more attractive and make students more enthusiastic about learning grammar in the future.Keywords: Grammo, Grammar mastery.